Time-course bicep tissue bio-impedance changes throughout a fatiguing exercise protocol. (July 2019) - Freeborn, Todd J.; Fu, Bo
Highlights: Bio-impedance measurements at 10 kHz, 50 kHz, 100 kHz collected at 11 timepoints from 17 participants biceps tissue throughout a fatiguing exercise protocol. Significant change in both resistance and reactance components of the impedance at each frequency compared to the pre-fatigue measurements. Significant changes in resistance observed at earlier timepoints than changes in the reactance. Abstract: This study investigated the localized electrical-impedance changes in the biceps tissues throughout a fatiguing exercise protocol. During the protocol, 17 subjects performed 10 sets of bicep curl repetitions at either 60% or 75% of their one-repetition maximum weight until task failure. The localized tissue impedance (resistance, reactance, phase angle) was measured at 10 kHz, 50 kHz, and 100 kHz immediately after each of 10 sets for comparison against the baseline pre-fatigue measures. A trend of decreasing resistance and reactance magnitude were observed, with greater changes occurring as the protocol progressed. Statistical testing demonstrated statistically significant changes in resistance, reactance, and phase angle for both groups of participants. The significant changes in resistance were observed at earlier time-points than the reactance and phase angle changes for both groups.